The Development of Learning Solar System Augmented Reality for Elementary School - Agus Rineng Mattola; Reza Andrea; Budi Rachmadani (Politeknik Pertanian Negeri Samarinda, 2021)
Along with today's technological developments, applications can be used as a medium of learning. This study aims to create a learning application about the solar system by utilizing technology Augmented Reality which is expected to be used to support the Natural Science (IPA) learning program by an elementary school educational institution to make the teaching and learning system more creative and interactive. In this study, the method augmented reality used is Image Based Tracking, which uses images as markers. The tools that help in the making of this AR are the Vuforia SDK which is used as a storage area marker. By doing this research, the results obtained in the form of the Solar System Learning application Augmented Reality that runs on the platform Android and testing respondents using the method User Acceptance Testing (UAT)with a value of 73.5%.